1 views

Uploaded by Yoyo Kirby2

Calculus

Calculus

© All Rights Reserved

- Erick Lin Resume
- Erick Lin (Middle)
- Erick Lin
- 04 Greedy Algorithms i i
- A Modern Approach to Quantum Mechanics
- Airport Brochure
- Professional Summary
- Wolf Rayet Stars
- 8. Pg. 492 #5, 6
- 7. Cosine Convergence Graphs
- 6. Pg. 386 #17
- 5. Derivation of the Logistic Growth Model
- 3. Slope Fields
- 4. Euler's Method Examples
- 1. Integration Techniques
- 4. Large-Scale Universe (Chps. 23-26)
- 3. Properties of Stellar-Mass Objects (Chps. 19-22)
- 2. Measuring the Stars (Chps. 16-17)
- 1. Fundamental Concepts (Chps. 1-4)
- Dynamic Planet Notes

You are on page 1of 3

solved by integrating with respect to the variable of integration. The solution is an equation that

relates the variables in a way that their derivatives will satisfy the differential equation. The

additional information needed to completely solve a differential equation is an initial condition,

which is usually given as the value of the function at a single point; a differential equation with

an initial condition is also called an initial value problem.

A differentiable equation is separable if its variables can be separated onto opposite sides

of the equation. After this is done, the solution can be found by using ordinary techniques to

integrate each side separately.

1)

dy x 2

=e ( y y ) , y ( 0 ) =2

dx

dy

=e x dx

y ( y1 )

A

B

1

+

=

y y1 y ( y 1 )

Partial fraction

decomposition

A ( y1 ) + By=1

A ( 01 ) + B ( 0 )=1

y=0

A=1

A ( 0 ) + B (1 ) =1

y=1

B=1

1

+

dy= e x dx

(1

y y1 )

function.

ln| y|+ln | y 1|=e x +C

C=ln |1|ln |2|e0

Substitute values from the initial condition.

ln 21

x

ln | y1|ln| y|=e ln 21

solution.

Substitute for C

in the

2)

ds 2 s +2

=

dt t 2 +2 t

ds

dt

=

2 s+2 t ( t+ 2 )

A B

1

+

=

t t +2 t ( t +2 )

A ( t+2 ) + Bt =1

A ( 0+2 ) + B ( 0 )=1

t =0

A=

1

2

A (2+2 ) + B (2 )=1

t=2

B=

ds

1

2

2 ( s+1 ) =

1

1

dt

2t 2 ( t + 2 )

1

1

1

ln |s +1|= ln|t| |t+ 2|+C

2

2

2

dv

2

= ( v +1 ) sin t

, where t

dt

represents

t=

the time elapsed. If v =0 at time

2 , determine the equation for the particles velocity.

dv

( v +1 )2 = sin t dt

1

=cos t+C

v +1

C=

+cos

0+1

2

Integrate both sides.

Substitute values from the initial condition.

1

=cos t+ 1

v +1

1

1=v

cos t+1

v=

cos t

cos t+1

Solve for v .

- Erick Lin ResumeUploaded byYoyo Kirby2
- Erick Lin (Middle)Uploaded byYoyo Kirby2
- Erick LinUploaded byYoyo Kirby2
- 04 Greedy Algorithms i iUploaded byYoyo Kirby2
- A Modern Approach to Quantum MechanicsUploaded byYoyo Kirby2
- Airport BrochureUploaded byYoyo Kirby2
- Professional SummaryUploaded byYoyo Kirby2
- Wolf Rayet StarsUploaded byYoyo Kirby2
- 8. Pg. 492 #5, 6Uploaded byYoyo Kirby2
- 7. Cosine Convergence GraphsUploaded byYoyo Kirby2
- 6. Pg. 386 #17Uploaded byYoyo Kirby2
- 5. Derivation of the Logistic Growth ModelUploaded byYoyo Kirby2
- 3. Slope FieldsUploaded byYoyo Kirby2
- 4. Euler's Method ExamplesUploaded byYoyo Kirby2
- 1. Integration TechniquesUploaded byYoyo Kirby2
- 4. Large-Scale Universe (Chps. 23-26)Uploaded byYoyo Kirby2
- 3. Properties of Stellar-Mass Objects (Chps. 19-22)Uploaded byYoyo Kirby2
- 2. Measuring the Stars (Chps. 16-17)Uploaded byYoyo Kirby2
- 1. Fundamental Concepts (Chps. 1-4)Uploaded byYoyo Kirby2
- Dynamic Planet NotesUploaded byYoyo Kirby2